La voix de la mère dans À la Recherche du Temps perdu (Journal of the College of Languages (JCL), 2014)
AbstractThe twentieth century French novel had undergo a significant change that took the form of a radical move from the traditional son who follows his father to one who no way prevalent in the classical French novel. The new son in the 2Oth century novel finds himself emotionally attached which both became a new trend and approach in novel writing.Marcel Proust's novel which can be considered a source of inspiration for most of 2Oth century novelists is a good example of the mother supremacy which is crystal clear from the first page through its parts and chapters till the last page. In fact, Proust had written a completely different novel from the Balzacian conventions. Unlike the latter's novels, Proust's are characterized by the omnipresent of mother and the absence of the father.Hence,Proust's novel can be considered a turning point in the novel writing. More over, the supremacy of the mother and the enhancement of its authority resulted in supremacy of the interior dialogue as a narrative technique.The presence of the mother in the son's consciousness contributes to the deeping of his feeling of his self-attachment. As long as the sense of guilt is strong, the return to the innermost of one's being where he can invoke his childhood and mother will be strong.The presence of the mother in the novel created an inner realm for the son who keeps resorting to his mother's memory even after her absence during his journey into the corridors of the self. When Marcel loves a girl called Albertin,he becomes prey to his deep feeling of guilt. He was afraid that his noble love so as to make the mother eternal in the hero's consciousness.Marcel has discovered the value of the past from his close relationship to his mother and childhood which represent a new direction of life for him. He can create out of it beautiful works if he only knows how to invest time.Hence,the hero in Proust's novel is able to regain the sense of security from the retrospective past due to the presence of the eternal mother who memory become a shine made of paper to which thousands of readers make a pilgrimage.